Boundary element solution for periodic acoustic problems. (6th January 2016) - Karimi, M.; Croaker, P.; Kessissoglou, N.
Abstract: This work shows when using the boundary element method to solve 3D acoustic scattering problems from periodic structures, the coefficient matrix can be represented as a block Toeplitz matrix. By exploiting the Toeplitz structure, the computational time and storage requirements to construct the coefficient matrix are significantly reduced. To solve the linear system of equations, the original matrix is embedded into a larger and more structured matrix called the block circulant matrix. Discrete Fourier transform is then employed in an iterative algorithm to solve the block Toeplitz system. To demonstrate the effectiveness of the formulation for periodic acoustic problems, two exterior acoustic case studies are considered. The first case study examines a continuous structure to predict the noise generated by a sharp-edged flat plate under quadrupole excitation. Directivity plots obtained using the periodic boundary element method technique are compared with numerical results obtained using a conventional boundary element model. The second case study examines a discrete periodic structure to predict the acoustic performance of a sonic crystal noise barrier. Results for the barrier insertion loss are compared with both finite element results and available data in the literature.